Allelopathic effects of six alfalfa varieties at three stubbles on the germination, seedling and root growth of green foxtail and barnyardgrass. - Meixuan Li; Xiaohan Gai; Qian Bai; Fanru Xu; Shipu Cheng; Fuhong Miao; Qingwei Liang; Juan Sun; Yufang Xu (PLoS ONE)
Alfalfa (Medicago sativa) is known to release allelopathic substances to affect the germination and growth of other plants, which have the potential to be applied in controlling weeds. Green foxtail (Setaria viridis) and barnyardgrass (Echinochloa crus-galli), as malignant weeds worldwide, also pose a serious threat to alfalfa in northern China. In this study, the sensitivity of the two weeds to the extracts from the first, second, and third stubbles of six varieties were investigated to further reveal the allelopathic interference of different varieties of alfalfa on notorious weeds. The germination rate, the length and fresh weight of seedlings, the length and fresh weight of roots were measured to elucidate the allelopathy of alfalfa extracts on the two weeds. The results suggested that: (1) The allelopathy of six alfalfa varieties tested showed obvious intraspecific differences, the inhibition of Zhongmu No.3 on green foxtail and barnyardgrass was weaker than other varieties, with the values of synthetical allelopathic effect (SAE) were -0.55 and -0.29, respectively. (2) The inhibitory effect of alfalfa extracts on green foxtail was enhanced with the increase of stubbles, while the differences between three stubbles on barnyardgrass were not clear, especially between the first and second stubbles. (3) Compared with barnyardgrass (SAE = -0.39 ~ -0.29), green foxtail (SAE = -0.65 ~ -0.52) was generally more susceptible to the extracts. (4) The inhibitory effect of alfalfa extracts on root was stronger than seedling in the same weed. For example, the third stubble extracts of Baoding variety inhibited 88.00% of the roots at the concentration of 0.01 g mL-1, but did not affect the seedlings of green foxtail. The study may help to comprehensively reveal the allelopathic effect of different alfalfa varieties in the first three stubbles on green foxtail and barnyardgrass, providing scientific evidence for weed control based on natural plant extracts in the future.